Análise intersetorial dos fluxos de água virtual para a economia brasileira: uma abordagem insumoproduto - Moraes, Vanessa de Oliveira (2015)
Water is a major input used directly and indirectly by the different sectors of the economy to produce goods and services. The use of this resource as a productive input is known as virtual water. This concept was developed by Allan (1993) and it refers to the water that is embedded or embodied in the production of agricultural commodities and industrial goods. The aim of this study is to apply an environmental input-output model to analyze water use in the Brazilian economy as well as to quantify the virtual water content in Brazil's imports and exports. The results indicate that Agriculture is an important key-sector, since, through the analysis of the matrix of coefficients transaction, it is possible to verify that it does mostly push the indirect water consumption of the majority of sectors. As for international trade of water resources, it comes out that Brazil is a net exporter of virtual water and that the largest share of exports is carried out by Food and Beverages sector and by Agriculture. Results suggest that Brazil is a virtual water net exporter, and most of the exports are made by Food and Beverage industries and Agriculture. These results reinforce the need to consider environmental costs that are inherent to trade goods in the use of water resources and a better management of water under scarcity conditions.